Utilization Of Energy And Nitrogen Of Setaria Sphacelata Var. Splendida Based Diets By Dairy Bulls - Mamat, Mustapha (1987)

(untitled)
Three experiments were conducted at the Dairy Farm, Department of Animal Sciences , Universiti Pertanian Malaysia , Serdang , using four cross-bred dairy bulls , Jersey O X Local Indian Dairy Q. The main objective o f the study was to evaluate the effects of nitrogen fertilization and supplementation with urea and leucaena on the nutritive value and utilization of Setaria sphacelata var . splendida in cattle . The indices measured included rumen degradability , in vivo digestibility , feed intake and the concentration of ammonia-N in the rumen liqour . In the balance studies , nitrogen intake and nitrogen balance were determined . The results o f Experiment I showed that the yields o f dry matter and nitrogen of the fertilize d were higher than those of the unfertilized forages , but the response ( kg per kg nitrogen applied) in both dry matter and nitrogen was decreasing with increasing nitrogen fertilization . The highest response in dry matter was recorded at 26 . 6 kg/kg N applied; while that for crude protein was 4 . 0 kg/kg N applied . The highest nitrogen recovery was found to be 64 . 2 kg N / 100 kg applied . These were achieved at the fertilization rate o f 250 kg N/ha per year .